Handover analysis over mobile WiMAX technology. - Chourio Chavez, Miguel Angel (My University, 2014)
As new mobile devices and mobile applications continue to growth, so does the data traffic demand for broadband services access and the user needs toward mobility, thereby, wireless application became today the fastest solution and lowest cost implementation unlike traditional wired deployment such as optical fibers and digital lines. WiMAX technology satisfies this gap through its high network performance over the air interface and high data rates based on the IEEE 802.16-2004 standards, this original specification does not support mobility. Therefore, the IEEE introduces a new standard that enables mobility profiles under 802.16e-2005, from which three different types of handovers process are introduced as hard handover (HHO), macro diversity handover (MDHO) and fast base station switching (FBSS) handover. The objective of this master thesis is to analyze how the handover process affects network performance. The analysis propose three scenarios, built over OPNET simulator to measure the most critical wireless parameter and performance indicator such as throughput, handover success rate, packet drop, delay and network usage.
Keywords: Base station; Scenarios; Handover; IEEE; MAC Layer; Mobile Station; Network; Performance; Physical Layer; QoS; Simulation; Throughput; WiMAX; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|; fi=Master's Degree Programme in Telecommunication Engineering|en=Master's Degree Programme in Telecommunication Engineering|